A Student Information Management System Based on Fingerprint Identification and Data Security Transmission - Pengtao Yang; Guiling Sun; Jingfei He; Peiyao Zhou; Jiangjiang Liu (Journal of Electrical and Computer Engineering)
A new type of student information management system is designed to implement student information identification and management based on fingerprint identification. In order to ensure the security of data transmission, this paper proposes a data encryption method based on an improved AES algorithm. A new S-box is cleverly designed, which can significantly reduce the encryption time by improving ByteSub, ShiftRow, and MixColumn in the round transformation of the traditional AES algorithm with the process of look-up table. Experimental results show that the proposed algorithm can significantly improve the encryption time compared with the traditional AES algorithm.